Insecurity and Major Determinants of Foreign Direct Investment in Nigeria - Olubunmi, Ayoola Adebukola (International Journal of Humanities and Social Science Research, 2019)
This paper investigated the major determinants of foreign direct investment (FDI) in Nigeria from 1999 to 2014 about the high rate of insecurity in the country within the period. The paper used both primary and secondary data which were analysed by qualitative and descriptive method while internalisation theory and Dunning eclectic paradigm provided bases for analysis. Findings revealed that insecurity has not significantly affected in-flow of FDI due to the country's unique characteristics that strengthen the lure of profits in investors over the risk of attacks. However, the prevalence of insecurity provided leeway for foreign investors to engage in sharp practices at the expense of the government and the people of Nigeria.